2022
DOI: 10.1001/jamaoncol.2021.3547
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of TRC105 Plus Pazopanib vs Pazopanib Alone for Treatment of Patients With Advanced Angiosarcoma

Abstract: This randomized clinical trial investigates whether carotuximab plus pazopanib improves progression-free survival vs pazopanib alone in adult patients with advanced angiosarcoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…This is of less concern as various studies that exploited CD105 for therapeutic applications reported little to no adverse effects (38,48). Similarly, the monoclonal antibody TRC105 was well-tolerated in monotherapy and combination therapy in clinical trials (53,54). Here, we confirmed that this CTL-based therapy against CD105 did not impact the wound- healing capacities of the mice, nor did it affect the overall health of experimental mice (Figure 8).…”
Section: Discussionsupporting
confidence: 73%
“…This is of less concern as various studies that exploited CD105 for therapeutic applications reported little to no adverse effects (38,48). Similarly, the monoclonal antibody TRC105 was well-tolerated in monotherapy and combination therapy in clinical trials (53,54). Here, we confirmed that this CTL-based therapy against CD105 did not impact the wound- healing capacities of the mice, nor did it affect the overall health of experimental mice (Figure 8).…”
Section: Discussionsupporting
confidence: 73%
“…A recent multicenter, phase 2 study evaluating pazopanib for uncurable angiosarcoma reported median PFS of 14.4 weeks and 3‐month PFS of 54.6% (95% CI 36.0–82.9%) 18 . In another clinical trial, the median PFS was 4.3 months with pazopanib for chemotherapy‐resistant angiosarcoma 19 . The median PFS was 132 days (4.4 months) in the present study, suggesting that the efficacy of pazopanib is comparable to that seen in previous clinical studies, even in a Japanese cohort 18,19 .…”
Section: Discussionmentioning
confidence: 99%
“…In March 2022 the TAPPAS trial a phase 3, multinational, multicentre, open label, parallel group trial reported the efficacy and safety of TRC105 (carotuximab, an IgG1 antibody binding to endoglin) combined with pazopanib compared to treatment with pazopanib alone in patients with advanced angiosarcoma (89). However, the results were disappointing whilst the PFS (primary endpoint) was not improved with treatment with carotuximab combined with pazopanib compared to pazopanib alone.…”
Section: Combinations Of Immune Checkpoint Inhibitors With Targeted T...mentioning
confidence: 99%